"Reconsidering the National Historical Heritage of Uzbekistan in the Digital Space" (Multidisciplinary Journal of Science and Technology, 2025)
The digital era has transformed the ways in which societies interact with and reinterpret their historical heritage. In Uzbekistan, the processes of digitization, social media expansion, and online education have created new opportunities for the preservation and recontextualization of national historical identity. This paper explores how the digital space serves as a platform for rethinking Uzbekistan’s historical narrative and collective memory, analyzing its influence on youth consciousness and the public’s perception of the past. Through a combination of content analysis, digital ethnography, and educational discourse review, the study identifies emerging trends in the online representation of historical heritage and the challenges of maintaining authenticity and scholarly accuracy.